Latin American and contemporary literary criticism: interpellations of a scriptural exercise (El Taco en la Brea, 2024)
In this work I propose to share a reflection on some critical lines that are developed in Latin America and that deal with readings made from various Latin American textual materialities. The objective is to investigate the ways in which it is possible to carry out readings that involve a «risk» or «a leap into the void» since these are critical operations that involve reading «another way» and from other corpora of contemporary Latin American literature. moments difficult to define from the theoretical frameworks that criticism generated during the last decades of the 20th century. Within the context of a strongly globalized society and located in the capitalist system in its contemporary version, in this communication I intend to share some notes for a reflection that is based on the demands of the literary materials that we select to develop our research work. But, above all, this article attempts to delve into certain operations of critical writing in our contemporaneity as a way of reflecting on it. For this purpose, a textual tapestry inspired by the methodology of contrastive comparatism that Marcela Croce presented in her book Comparatismo contrastivo. Manual para una práctica urgente published in 2023.
Keywords: literary criticism; contemporary Latin American literatura; writings; critical operations; contrastive comparatism